Ketepatan dan konsistensi pukulan forehand topspin dalam tenis meja: studi perbandingan antara atlet pria dan wanita - Jeki Haryanto; Friski Amra; Naluri Denay; Eval Edmizal (Indonesian Institute for Counseling, Education and Theraphy, 2025)
Background: Topspin is a fundamental stroke technique in table tennis with a critical role in match outcomes. However, descriptive profiling of topspin performance across repeated trials and gender differences remain underexplored in Indonesian sport science literature. Objective: This study aimed to describe topspin performance profiles in table tennis athletes, analyze performance consistency across 10 repeated trials, and compare topspin performance between male and female athletes. Methods: This descriptive quantitative study involved 56 table tennis athletes (male n=30, female n=26). Each participant performed 10 topspin trials scored 0–3 per trial (maximum total score 30). Statistical analyses included descriptive statistics, independent samples t-test, and repeated measures ANOVA. Results: Overall mean total topspin score was 18.57 (SD=3.28). Male athletes scored significantly higher (M=19.90; SD=3.22) than females (M=17.04; SD=2.66), with t(54)=3.591, p=.001. Cross-trial analysis revealed mild fluctuation with performance peaks at Trial 5 (M=2.125) and Trial 10 (M=2.036). An average total topspin score of 18.57 out of a maximum score of 30 (SD=3.28) indicates that the participants were overall at a medium level of performance. Conclusion: Significant gender differences in topspin performance were identified, with males outperforming females. Performance patterns across trials reflect motor learning principles and warm-up effects. Findings have important implications for coaches designing systematic, gender-differentiated topspin training programs.